Investigating the relationship between form and content in interactive graphic with a semiotic approach. (29th October 2019) - Jahangiri, Sara; Emamifar, Seyyed Nezamodin
In this research, the relationship between form and content in interactive graphic arts is examined from the semiotics point of view. This research has studied the importance of the relationship between form and content in the formation of interactive graphic in semiotics and it has also dealt with the work of the relationship between form and content in the formation of virtual reality and the position of audience in interactive graphics and the recognition of the passwords and the interpretation of the signs by which the content is determined. The research methodology is based on the descriptive-analytical nature and data collection which is done through combined method (library and field) and the number of samples are six images. The data analysis method has also been qualitative approach. The results of examining the samples show that in most of them, the relationship between form and content in interactive graphics from the semiotics point of view is to create visual shock to the audience. And for inducing the concept, the dominant mode is also the use of indexing elements.